Studying the serum ghrelin levels of the elite athletes and sedentary controls fasting at the time of Ramadan - C. Berkan Alpay; Hasan Eker; İbrahim Cıcıoglu; İlhan Yetkın; Ozlem Gulbahar (Türk Spor ve Egzersiz Dergisi)
The Ghrelin is produced primarily by enteroendocrine cellsin the gastric mucosa, and increases gastric emptying in normal subjects.The purpose of this study is to determine the differences in the Ghrelin level during different times along the day, and to assess the differences between the athletes and sedentary at the end of Ramadan fasting period of one month. The results indicated that there were no significant difference among the Ghrelin levels of athletes and sedentary during different times through the day (p gt;0.05). Significant differences were observed between pre- and post-tests mean Ghrelin scores of subjects (p lt;0.05) without making a separation as an athlete and sedentary. Also, the results indicated no significant difference between repeated Ghrelin measurements of athletes and sedentary (p gt;0.05). A significant and positive relationship was found in the middle level at the percentages of BMI and body fat of both groups. Moreover, there were significant differences among BMI scores (p lt;0.01) and body fat % (p lt;0.05) of the athletes and sedentary. Consequently, fasting during Ramadan did not cause any differentiation on the serum Ghrelin level of athletes and sedentary, but without group differentiation there was significant increase from the initial measurement to the last measurement of the serum Ghrelin level. There was a significant and positive relationship at middle level between BMI and body fat % of both groups of athletes and sedentary. There was a significant relationship, on the other hand, between BMI and repeated Ghrelin measurements of subjects.